Narcotics Brokers and Logistics Routes in Indonesia: Legal System Weaknesses from Ḥifẓ al-'Aql Perspective - Muhammad Hasan Nasution; Mhd Syahnan; Mustafa Kamal Rokan (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2025)
This study examines the roles of brokers and logistics routes in Indonesia's narcotics supply chain, which has evolved into a transnational network connecting Golden Triangle production centers (particularly Myanmar's Shan State) with domestic markets through intermediate distribution nodes. The research employs a normative juridical method supported by a socio-legal approach and qualitative analysis, utilizing data from UNODC, BNN (National Narcotics Agency), Customs, and previous research reports to analyze the intersection of global economic dynamics, legal system weaknesses, and narcotics trafficking operations. Findings reveal that brokers serve three critical functions: connecting international manufacturers with domestic markets, controlling pricing mechanisms, and designing logistics routes through major ports (Tanjung Priok, Batam) and minor harbors across maritime and air channels. Indonesia's consumer market comprises approximately 3.3 million narcotics users (1.73% of the population aged 15-64 years), with high prevalence rates in North Sumatra (6.5%), South Sumatra (5%), and DKI Jakarta (3.3%). However, law enforcement remains concentrated at the downstream level, with over 70% of prosecuted cases targeting users and couriers rather than intermediate brokers. Legal system weaknesses—particularly in Money Laundering (TPPU) instruments, customs supervision, and international cooperation—enable brokers to exploit regulatory gaps and maintain network resilience despite increased arrests. From the Maqasid Syariah perspective, specifically the principle of Hifz al-'Aql (protection of reason), this study proposes non-penal policy reconstruction emphasizing preventive, educational, and rehabilitative approaches that extend beyond criminal sanctions to protect community morals, reason, and welfare through structural reforms in financial regulation, logistics supervision, and international legal diplomacy.